Guide to industrial relations in Trinidad and Tobago - Brady, Jim (James A. Brady Port of SpainTT, 1988)
Traces the major industrial relations developments in Trinidad and Tobago from 1965 onwards, focusing on the changes in statutes and practices. Discusses strikes, worker protection, compulsory arbitration, and the Industrial Relations Act. Contains A to Z catalogue of explanations of the language, practices, and institutions governing industrial relations in Trinidad and Tobago.